The Slippage of Bolts on Axial Compression Capacity of Equal Angle Section’s Bolt Connection - Usman, Fathoni; Devi, Debby Sinta (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
Steel angles play a vital role in energy infrastructure, especially in latticed transmission towers where they act as axial compression members. Their structural performance is strongly influenced by end restraints, bolt configurations, and slenderness ratios, which affect buckling behavior and compression strength. This study examines how the number and arrangement of bolts, along with slenderness variations, impact the displacement and stress response of steel angles under compression using nonlinear analysis and finite element modeling. The investigation highlights that different bolt patterns and slenderness ratios significantly alter the stability and load-bearing capacity of the members. Single-row bolt configurations tend to experience greater slippage compared to multi-row setups, indicating the importance of connection design in preventing premature failures. Overall, the findings emphasize the need for optimized bolt arrangements and slenderness control to enhance resistance to buckling and improve the overall efficiency and reliability of energy infrastructure systems under axial compression loads.